GAMBARAN PENGELOLAAN OBAT ANALGETIK NSAID DI APOTEK RIZKY PENI FARMA PLESUNGAN TAHUN 2024: NSAID ANALGESIC MEDICATION MANAGEMENT AT RIZKY PENIFARMA PHARMACY IN PLESUNGAN IN 2024 - Desti Anggi Safitri; Risma Sakti Pambudi; Khotimatul Khusna (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2026)
Drug management in pharmacies is crucial to ensure the availability of appropriate medicines for the public. This study aimed to determine the procurement, storage, and use of NSAID analgesic drugs at Rizky Peni Farma Pharmacy in Plesungan in 2024. The research method used was a descriptive study with qualitative and quantitative approaches conducted retrospectively. Data were analyzed by comparing the results of observations with the Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016 concerning Pharmaceutical Service Standards in Pharmacies. The results showed that drug procurement was carried out through Pharmaceutical Wholesalers (PBF) following appropriate procedures. Drug storage was conducted using the FIFO (First In First Out) and FEFO (First Expired First Out) systems. The highest use of NSAID analgesic drugs was found in tablet form, both generic (6,780 tablets) and branded (11,300 tablets). The most commonly used active ingredient was mefenamic acid, both in generic (2,020 preparations) and branded (4,510 preparations) forms. The most common generic NSAID analgesic was oxicam (2,880 preparations), while the most commonly used branded analgesic was mefenamate (4,510 preparations). The conclusion of this study indicates that medication management in pharmacies is in accordance with pharmaceutical service standards. Keywords: Medication; Medication Management; NSAID Analgesics; Pharmacy